New concepts in the diagnosis and management of choroidal metastases. (January 2019) - Mathis, Thibaud; Jardel, Pauline; Loria, Olivier; Delaunay, Benoit; Nguyen, Anh-minh; Lanza, Francesco; Mosci, Carlo; Caujolle, Jean-Pierre; Kodjikian, Laurent; Thariat, Juliette
Abstract: The most frequent site of ocular metastasis is the choroid. The occurrence of choroidal metastases has increased steadily due to the longer survival of metastatic patients and the improvement of diagnostic tools. Fundoscopy, ultrasonography, and fluorescein angiography are now complemented by indocyanine green angiography and optical coherence tomography. Choroidal tumor biopsy may also confirm the metastatic nature of the tumor and help to determine the site of the primary malignancy. There is currently no consensus on the treatment strategy. Most patients have a limited life expectancy and for these complex treatments are generally not recommended. However, recent advances in systemic therapy have significantly improved survival of certain patients who may benefit from an aggressive ocular approach that could preserve vision. Although external beam radiation therapy is the most widely used treatment, more advanced forms of radiotherapy that are associated with fewer side effects can be proposed in select cases. In patients with a shorter life expectancy, systemic therapies such as those targeting oncogenic drivers, or immunotherapy can induce a regression of the choroidal metastases, and may be sufficient to temporarily decrease visual symptoms. However, they often acquire resistance to systemic treatment and ocular relapse usually requires radiotherapy for durable control. Less invasive office-based treatments, such as photodynamic therapy and intravitreal injection of anti-VEGF, may also help to preserve vision while reducing time spent in medical settings for patients in palliative care. The aim of this review is to summarize the current knowledge on choroidal metastases, with emphasis on the most recent findings in epidemiology, pathogenesis, diagnosis and treatment. Highlights: Choroid is the most common ocular site for metastatic spread, especially for breast and lung cancer. Enhanced imaging of the choroid allows better understanding and precise diagnosis of choroidal metastases. In case the primary remains unknown, tumor biopsy may help identify the primary and guide treatment. To date, fractionated radiotherapy remains the treatment of choice for choroidal metastases. The place of systemic targeted therapy and "office-based" treatment such as PDT or intravitreal antiVEGF should be considered.